Non-invasive serum potassium concentration measurement in children with CKD by quantifying T-wave morphology dynamics - Yue Xi; Zhen Liu; Jie Ni; Yang Miao; Zhi Chen (EngMedicine)
This study investigated the relationship between electrocardiography (ECG) and serum potassium levels in 100 children aged 6–18 years with chronic kidney disease admitted to the Department of Nephrology, Beijing Children's Hospital Affiliated, Capital Medical University, China. The research data were obtained from children in their growth and development stages with significant differences in their physical characteristics. We established a promising indicator, Ts/a, calculated Ts/a for V2–V6 in 100 children, and correlated it with their serum potassium levels. Despite significant differences in age and body shape between developing children and adults, the results showed that the Ts/a values of V5 and V6 were more strongly correlated with blood potassium values. T wave at the V5 and V6 leads in children can reflect the direction of the primary amplitude of the T-wave and T-wave downward slope, and the heart space position in the chest characteristics during childhood lead to these results. This study provides an essential foundation for the future mobile monitoring of serum potassium levels.